Kajian Kecenderungan Keusahawanan di Kalangan Pesara Tentera - Hapzarizal, M. Napi (2012)
The purpose of this study is to identify the tendency of entrepreneurship among military retirees in the entrepreneurial program organized by the Department of Veterans Affairs Malaysian Armed Forces (JHEV ATM). They were ninety identified military retirees have attended this course was chosen as respondents. The study was conducted using questionnaires instruments where all respondents are given a set of survey questions through the Entrepreneurship Unit staff handling JHEV entrepreneurship program. Received a response rate was 45% and the data obtained from this survey were analyzed by using Statistical Package for Social Science (SPSS). The results showed that the tendencies of entrepreneurship among military retirees are moderately high level. Factors such as pension income, education level, family background in business and business experience before leaving the Malaysian Armed Forces (ATM) as an independent variable in determining entrepreneurial intention. Of the four factors, all of these factors have been identified as the trigger influence entrepreneurial tendencies among respondents. The level of entrepreneurship in higher average level is greatly influenced of pension income by available are insufficient to meet the high family expenses within the Klang Valley.